Mutiny and Aftermath : James Morrison's Account of the Mutiny on the Bounty and the Island of Tahiti - Morrison, James, 1761-1807 (Book collections on Project MUSE., 2013)
The mutiny on the Bounty was one of the most controversial events of eighteenth-century maritime history. This book publishes an absorbing narrative of the events written by one of the participants, the boatswain's mate James Morrison, who tells the story of the mounting tensions over the course of the voyage out to Tahiti, the fascinating encounter with Polynesian culture there, and the shocking drama of the event itself. In the aftermath, Morrison was among those who tried to make a new life on Tahiti. In doing so, he gained a deeper understanding of Polynesian culture than any European who went on to write about the people of the island and their way of life before it was changed forever by Christianity and colonial contact. Morrison was not a professional scientist but a keen observer with a lively sympathy for Islanders. Morrison's "Journal" was composed before the trial three or four years after the events it narrates, probably from notes taken at the time of these events, though this is a supposition. This book is based directly on a close study of Morrison's original manuscript, one of the treasures of the Mitchell Library in Sydney, Australia. The editors assess and explain Morrison's observations of Islander culture and social relations, both on Tubuai in the Austral Islands and on Tahiti itself